Japan : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper analyzes reasons behind low levels of private investment in Japan. Private investment in Japan not only appears low, but also seems to have underperformed relative to other advanced economies. Findings support the hypothesis that sectoral concentration (reduced competition) has had a significant negative impact on firm- and sector-level investment. Results point to potential benefits from decreasing barriers to entry, protection of incumbents, and market concentration in some sectors. Results also indicate that there is room for further reform in the gas and telecom sectors, and deregulation of professional services.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet